Digital customer experience mapping in Russian premium banking - G. S. Timochina; Lyubov Prokopova; Yuri Gribanov; Stanislav Zaitsev; Natalia Ivashkova; Roman Sidorchuk; Irina Skorobogatykh; Anatoly Shishkin; Zhanna Musatova (Economies, 2021)
The purpose of this study is to identify, in an era of extensive digitalization, the major opportunities and threats that influence the experiences of digital premium banking customers at key stages of their banking interactions. This study's conceptual research model combines the content of online questionnaires, completed by a representative sample of 3629 customers, in-depth interviews with heads of premium banking departments, and an audit of customer experiences conducted via Mystery Shopping in 13 Russian banks. The authors formulate four research hypotheses, substantiated by the empirical data and highlight key barriers preventing premium banks from effective digital interactions with their customers. Key opportunities for improving customer experiences are also identified. The theoretical contribution of the research includes the adaptation of an axiological approach to studying digital customers in premium banking. Practical contributions include the Premium Digital Customer Experience Map, designed by the authors as a ready-made tool for planning and improving premium banking services and a tool for performance comparison between competing banks. This study also discusses the authors' definition of a "digital customer". It presents a new approach to the Mystery Shopping methodology, including the recruitment of Mystery Shoppers following the three premium banking customer portraits: "saver", "spender", and "saver-spender".
Keywords: 330; banking digitalization; digital customer; experience mapping; improving customer experience; key phases interactions; premium banking